2023
DOI: 10.1017/s0954579422001456
|View full text |Cite
|
Sign up to set email alerts
|

Do testosterone and cortisol levels moderate aggressive responses to peer victimization in adolescents?

Abstract: Aggressive reactions to peer victimization may be tempered by hormone levels. Grounded on the dualhormone hypothesis (DHH), which proposes that testosterone (T) is associated with aggressive behavior only when cortisol (C) is low, this study assessed whether the combination of T and C moderated adolescents’ aggressive responses to peer victimization. The study involved 577 adolescents (50.4% girls, aged 12–17 years), who completed measures of online and offline victimization and perpetration of aggressive beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Finally, a recent study explored the moderating effects of testosterone and cortisol on the association between bullying and aggressive behavior. Results showed that adolescents with high testosterone and cortisol levels or with low testosterone and cortisol levels responded more aggressively when victimized or provoked [30].…”
Section: Hpg-dependent Hormones and Bullyingmentioning
confidence: 97%
See 4 more Smart Citations
“…Finally, a recent study explored the moderating effects of testosterone and cortisol on the association between bullying and aggressive behavior. Results showed that adolescents with high testosterone and cortisol levels or with low testosterone and cortisol levels responded more aggressively when victimized or provoked [30].…”
Section: Hpg-dependent Hormones and Bullyingmentioning
confidence: 97%
“…Only three studies [29][30][31] have analyzed the role of HPG axis-dependent hormones in bullying behavior. All three studies measured testosterone levels in saliva, and one of them measured the participants' 2D:4D ratio as an indicator of prenatal sex hormones [29].…”
Section: Hormones Assessmentmentioning
confidence: 99%
See 3 more Smart Citations